Framing the pandemic in the political discourse of Justin Trudeau and Donald Trump: A reconnaissance - Kasztenna, Katarzyna (Kasia) (Working papers in Applied Linguistics and Linguistics at York, 2022)
Employing the tools of discourse analysis, this paper seeks to investigate the framing strategies mobilized by Justin Trudeau and Donald Trump in their speeches delivered in response to the announcement of the global pandemic of COVID-19 on March 11, 2020. The author contrasts the frames of war and the frames of rational positivistic reaction to the challenge, exploring lexical choices, topoi, and larger discursive structures such as myths and ideologies to restore the storylines underpinning both texts. The analysis reveals the deeply instilled divergence of the vision of a nation, history, and the role of public institutions in both speeches.